Social networks and their implications for community living for people with a learning disability. (April 2015) - Dunbar, Robin
Abstract : The human social world is complex and multi-layered, and requires specialised skills to allow us to handle it successfully. This places limits on the size of network that individuals can manage, with a typical network size of around 150 individuals. Kinship plays a crucial role in these networks, with about half of the typical network being family members. By comparison with family relationships, friendships are fragile and deteriorate rapidly when contact rates fall below the rather specific frequencies needed to maintain them. Friendships exhibit strong homophily effects, with the quality of friendships being determined by the number of shared traits. The willingness of both family and friends to act altruistically towards others depends on their shared interests, but there is always a 'kinship premium' (kin are always more generous towards family members). I explore the implications of these structural aspects of natural human social networks for people with a learning disability.